Perfunctory gamification in the world of second language learning - Opacki Marcin (Journal of China Computer-Assisted Language Learning)
Gamification is a trend that is steadfastly increasing in popularity in several fields that involve learning. Several concepts borne out of this have recently been applied with the intent to facilitate second language learning. This is most notably visible in the form of apps and online teaching courses that take advantage of mechanics that are drawn directly from video game design principles. In the context of language learning, the incorporation of game mechanics can be used to construct effective systems of incentive and ultimately enrich the FL learning experience in various ways, potentially resulting in improved outcomes. However, the prevailing trend in the gamification of language learning apps is to rely on a Black Hat gamification mechanics. These are propagated without much reflection in manner that can only be described as perfunctory gamification. Nevertheless, the subpopulation of so-called hardcore gamers is not only unsusceptible to these techniques, but exhibits a strong aversion to them. As a result, hardcore gamers are for the most part functionally excluded from the pool of potential CALL app users. The present work outlines several potential solutions to the problem of perfunctory game design practices that alienate hardcore gamers. Chief among these is the proposal to actively work towards a paradigm shift from gamification towards game-based learning.